Antigua and Barbuda : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper describes economic developments in Antigua and Barbuda during the 1990s. Economic performance deteriorated in the early 1990s. Output growth slowed to 4 percent a year in 1992-94, as activity in the tourism sector slackened and public investment fell because of a poor public savings performance and reduced access to foreign financing. Despite the slowdown in activity, growth in private sector wages exceeded inflation during this period, owing partly to the effect of employment and real wage increases in the government sector.